Young colonization history of a widespread sand dollar (Echinodermata; Clypeasteroida) in western Taiwan. (10th September 2019) - Lee, Hsin; Lin, Jih-Pai; Li, Hong-Chun; Chang, Lo-Yu; Lee, Kwen-Shen; Lee, Shyh-Jye; Chen, Wei-Jen; Sankar, Ammu; Kang, Su-Chen
Abstract: Arachnoides placenta is the most common sand dollar species in western Taiwan. Due to its lack of fossil record, the arrival of this species in Taiwan could not be estimated until now. Fragments of A. placenta was recovered sorting through a 1981- museum collection of sand dollars collected off Mailiao county, western Taiwan. Additional echinoderm specimens were recovered from Holocene sediments nearby, but no fragments of A. placenta were found, indicating a decline in the living population. A total of 11 echinoderm samples, including five specimens that were assigned to A. placenta with certainty, were sent for radiocarbon dating. Results showed that studied echinoderm fragments range from modern (after 1950) to as old as 2680 ± 55 a BP and the oldest date is from A. placenta . It is evident that Taiwan is an active migration front for A. placenta due to the relatively young arrival age for this pandemic species which is widespread in the Indo-West Pacific region. Additionally, the DNA sequence, including the cytochrome c oxidase subunit I (cox1) gene, of the species was obtained to conduct the first molecular phylogenetic study of sand dollars in Taiwan.